AKHLAK DALAM PENDIDIKAN AGAMA ISLAM - Afriandi; Amaliah, Nurul; Awaliah, Nur Israh; Sulfi; Santiani; Hidayat, Yusran; Ramadhan, Muh Faiz (Program Studi Pendidikan Teknologi Informasi Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
Moral issues are always linked to the social problems of society. Morals determine human value in the eyes of other humans. Morals are the soul's ability to give birth to an action spontaneously without any thought or coercion, an action that is born under the impulse of the soul in the form of a praiseworthy or despicable action. Morals are a reflection of a person's spiritual state which is applied in everyday life. According to Al Ikhlas, morals are the crown of humanity. There are two types of morals in Islam, namely akhlak karimah or what is called akhlak mahmudah (praiseworthy morals), namely morals that are good and correct according to Islamic teachings, secondly, madzmumah morals or akhlak (reprehensible) namely morals that are not good and correct according to Islamic teachings.